Highly Efficient Bifunctional Amide Functionalized Zn and Cd Metal Organic Frameworks for One-Pot Cascade Deacetalization–Knoevenagel Reactions - Karmakar, Anirban; Paul, Anup; Rúbio, Guilherme M. D. M.; Soliman, Mohamed M. A.; Guedes da Silva, M. Fátima C.; Pombeiro, Armando J. L. (Frontiers in Chemistry, 2019)
A pyridine-based amide functionalized tetracarboxylic acid, 5,5′-(pyridine-2, 6-dicarbonyl)bis(azanediyl)